USING PODCAST AS A STRATEGY TO IMPROVE EFL STUDENTS’ LISTENING SKILL - Rizkina Damayanti; Muhamad Sofian Hadi (STKIP PGRI Jombang, 2022)
AbstractA podcast is an audio file that is possible to download from the internet and can be defined as online audio blogging. The purpose of this study was to find information about the use of podcasts as a strategy to improve EFL students’ listening skill. The research method uses a descriptive qualitative approach where the collected data will be described in a narrative. As for the data sources in this study were obtained by analyzing and interviewing. The results of using podcasts as a strategy to improve EFL students’ listening skill are shown effectiveness and can help improve their listening skills.Keyword: Listening skill, podcast, EFL students AbstrakPodcast adalah file audio yang dapat diunduh dari internet dan dapat didefinisikan sebagai blog audio online. Tujuan dari penelitian ini adalah untuk menemukan informasi tentang penggunaan podcast sebagai strategi untuk meningkatkan keterampilan mendengarkan peserta didik EFL. Metode penelitian ini menggunakan pendekatan kualitatif deskriptif dimana data yang terkumpul akan dideskripsikan secara naratif. Adapun sumber data dalam penelitian ini diperoleh dengan cara analisis dan wawancara. Hasil penggunaan podcast sebagai strategi untuk meningkatkan keterampilan mendengarkan peserta didik EFL menunjukkan efektivitas dan dapat membantu meningkatkan keterampilan mendengarkan mereka.Kata kunci: Kemampuan mendengarkan, podcast, peserta didik EFL